EFEKTIVITAS MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA POST OPERASI - Kgs. Muhammad Faizal; Mulya (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Today a number of diseases indicate an indication for surgery. After surgery, the patient willexperience a weak condition and it will be difficult to carry out activities due to surgicalprocedures and surgical wounds that require time in the healing process. Data on general surgeryin 2018 were 445 patients with a stay of 3-5 days Nursing interventions that can be performed bypostoperative patients are early mobilization. Early mobilization includes factors that can affectthe surgical wound healing process. The purpose of this study was to determine the effectivenessof early mobilization on post operative wound healing. The design of this study was quasiexperimentalwith a post-test only control group design. The population was all postoperativepatients at the Depati Hamzah Regional Hospital in Pangkalpinang City. The sampling techniqueuses non random sampling by accidental sampling, with 12 respondents in the intervention groupand 12 respondents in the control group. The test used is the T test of two different dependentmeans. The results of the study were that there was a significant difference between woundhealing performed early mobilization and healing which was not carried out early mobilizationwith a p value: 0.002. The suggestion from this research is that a hospital can implement earlymobilization after 6 hours postoperatively, so that the wound healing time will be faster.